Economic Integration and the Transmission of Democracy - Marco Tabellini; Giacomo Magistretti; Giacomo Magistretti (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
In this paper, we study the effects of economic integration with democracies on individuals' democratic values and on countries' institutions. We combine survey data with country level measures of democracy from 1960 to 2015, and exploit improvements in air, relative to sea, transportation to derive a time-varying instrument for trade. We find that economic integration with democracies increases both citizens' support for democracy and countries' democracy scores. Instead, trade with non-democracies has no impact on either attitudes or institutions. The effects of trade with democracies are stronger when partners have a longer history of democracy, grow faster, spend more on public goods, and are culturally closer. They are also driven by imports, rather than exports, and by integration with partners that export higher quality goods and that account for a larger share of a country's trade in institutionally intensive, cultural, and consumer goods as well as in goods that involve more face-to-face interactions and entail higher levels of bilateral trust. These patterns are consistent with trade in goods favoring the transmission of democracy by signaling the (actual or perceived) desirability of the latter. We examine alternative mechanisms, and conclude that none of them can, alone, explain our findings.
Keywords: F14; F15; P16; 330; Democracy; political preferences; institutions; economic integration